1991
DOI: 10.1288/00005537-199108000-00017
|View full text |Cite
|
Sign up to set email alerts
|

P300 response to tones and speech sounds after cochlear implant: A case report

Abstract: P300 potentials evoked by tones and spoken words were recorded from a 20-year-old man with a House-3M single-channel cochlear implant. Three months after cochlear implantation, there was a slight appearance of P300 response to both pure-tone stimuli and spoken-word stimuli; 6 months later, clearly identifiable P300 response to both pure-tone stimuli and spoken-word stimuli were obtained. These results are consistent with an encoding improvement for re-establishment of information processing after auditory reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 6 publications
0
22
0
6
Order By: Relevance
“…Performance on behavioural tests of auditory processing is affected by factors such as task learning and motivation level. There is increasing evidence that auditory evoked potentials can be used as an objective, non-invasive tool to investigate auditory processing and plasticity of auditory function in humans [Eggermont et al, 1997;Jordan et al, 1997;Kaga et al, 1991;Kraus, 1999;Kraus et al, 1995Kraus et al, , 1998aMenning et al, 2000;Ponton et al, 1996aPonton et al, , b, 1999Ponton et al, , 2000aTremblay et al, 1997Tremblay et al, , 1998Tremblay et al, , 2001. Results from electroencephalographic evoked potential studies are consistent with magnetoencephalographic evidence for auditory plasticity in human listeners [Pantev et al, 1999[Pantev et al, , 2001Pantev and Lutkenhorner, 2000].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Performance on behavioural tests of auditory processing is affected by factors such as task learning and motivation level. There is increasing evidence that auditory evoked potentials can be used as an objective, non-invasive tool to investigate auditory processing and plasticity of auditory function in humans [Eggermont et al, 1997;Jordan et al, 1997;Kaga et al, 1991;Kraus, 1999;Kraus et al, 1995Kraus et al, , 1998aMenning et al, 2000;Ponton et al, 1996aPonton et al, , b, 1999Ponton et al, , 2000aTremblay et al, 1997Tremblay et al, , 1998Tremblay et al, , 2001. Results from electroencephalographic evoked potential studies are consistent with magnetoencephalographic evidence for auditory plasticity in human listeners [Pantev et al, 1999[Pantev et al, , 2001Pantev and Lutkenhorner, 2000].…”
Section: Introductionmentioning
confidence: 78%
“…There is evidence from both adults and children receiving cochlear implants that improvements in speech perception are accompanied by changes in cortical auditory evoked potentials [Eggermont et al, 1997;Jordan et al, 1997;Kaga et al, 1991;Ponton et al, 1996aPonton et al, , b, 1999Ponton et al, , 2000a. Ponton et al have found that P1 follows the normal sequence of development in implanted children once a cochlear implant is switched on, but P1 development is delayed by the time without sound.…”
Section: Effects Of Auditory Training and Experience On Auditory Evokmentioning
confidence: 99%
See 1 more Smart Citation
“…EABR studies on man have shown a waveform Task-related P300 measurements using tone bursts in patients with a Cl were performed by Kaga et al (14) and Oviatt and Kileny (11). It was argued that morphology which is comparable with that found the P300 latency might be related to Lhe phonemic during acoustic stimulation, but with shorter latencies and linguistic discrimination abilities of Cl patients (4, 6-10).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of late auditory potentials evoked with electrical stimulation have included recordings of the N1, P2, P300, and mismatch negativity (MMN) response elicited with pulsed tones (Oviatt & Kileny, 1991), stimulated electrode pairs (Makhdoum, Groenen, Snik, & van den Broek, 1997;Ponton & Don, 1995), and speech (Kaga, Kodera, Hirota, & Tsuzuka, 1991;Kraus et al, 1993;Micco et al, 1995). Results suggest that cortical responses provide a mechanism for understanding how electrical stimuli are registered by the central auditory system.…”
mentioning
confidence: 99%